2004
DOI: 10.3349/ymj.2004.45.5.822
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Urokinase Instillation Therapy via Percutaneous Transthoracic Catheter in Loculated Tuberculous Pleural Effusion: A Randomized Prospective Study

Abstract: The purpose of this study was to propose that intrapleural urokinase (UK) instillation could reduce pleural thickening in the treatment of loculated tuberculous pleural effusion. Forty- three patients who were initially diagnosed as having loculated tuberculous pleural effusion were assigned at random to receive either the combined treatment of UK instillation including anti-tuberculosis agents (UK group, 21 patients) or strictly the unaccompanied anti-tuberculous agents (control group, 22 patients). The UK gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 0 publications
3
21
1
Order By: Relevance
“…This more efficient drainage improved dyspnoea more rapidly, but did not shorten the duration of fever. These findings are in line with previous studies [5,10,11], and strongly suggest that anti-TB medication is the mainstay of treatment for the resolution of pleural inflammation in TB pleurisy, whereas early and effective pleural drainage, with or without streptokinase instillation, improves respiratory function but does not affect the intensity of the pleural inflammation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This more efficient drainage improved dyspnoea more rapidly, but did not shorten the duration of fever. These findings are in line with previous studies [5,10,11], and strongly suggest that anti-TB medication is the mainstay of treatment for the resolution of pleural inflammation in TB pleurisy, whereas early and effective pleural drainage, with or without streptokinase instillation, improves respiratory function but does not affect the intensity of the pleural inflammation.…”
Section: Discussionsupporting
confidence: 82%
“…The influence of therapeutic thoracentesis on the development of RPT has not been verified by previous studies [2][3][4][5]. However, two recent studies indicated that RPT occurred less frequently in patients with loculated TB pleurisy treated with intrapleural urokinase than in those with no drainage or those treated with simple drainage [10,11]. In the present study, 10 (45%) out of 22 patients in the saline group developed RPT.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Thirteen were then retrieved for full text review. Five [21][22][23][24][25] were then excluded because the study population consisted of mainly tuberculous pleural effusions, and one 26 was excluded because it did not have a control arm (ie, placebo) ( Fig 1 ). Thus, seven studies 7,[9][10][11][27][28][29] were included in the fi nal analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Kwak and associates randomized 43 patients with loculated pleural effusions to receive 100,000 IU urokinase daily, administered through a pigtail catheter, starting when the pleural fluid drainage was less than 100 mL/day and finishing when the amount of pleural fluid was less than 50 mL/ day, or only anti-TB therapy [78]. They concluded that the mean width of pleural thickening was 0.46 cm in the urokinase group and 1.86 cm in the control group [78].…”
Section: Treatment Chemotherapymentioning
confidence: 99%